Sistem Informasi Penjualan Berbasis Desktop pada Rumah Laundry Kiloan - Daulima, Gilbert; Purwandari, Nuraini (Institut Teknologi dan Bisnis Kalbis, 2020)
Rumah Laundry Kiloan is a business that offers laundry services. This business still uses aconventional transaction system. So that the system used in Rumah Laundry Kiloan still has shortcomingsand risks. The system used has the risk of losing customer notes, damage and loss of ledgers. This studyaims to help business processes that are running at Rumah Laundry Kiloan, so that they can overcomeproblems and reduce the risks of Rumah Laundry Kiloan by building a desktop-based sales informationsystem that includes saving transactions, adding transactions, adding customer data, store customerdata, and all fields included in the transaction. The system development method used is a prototypedevelopment method. The results of this study are an information system that can be used by RumahLaundry Kiloan that have been tested with black box testing.